Velo City Architecture for Bikes. - Blyth, Gavin (Prestel, 2014)
From a bike rack to the world's most glamorous cycling shop, Velo Architecture shows how our cities are being transformed by a new wave of bike-related design. The world's major cities are making room for cyclists, helping them to ride, store, share, and buy their bicycles more easily than ever before. As a result, bike-related design has become one of the hottest fields in architecture. From racetracks to commuter paths and from bike sharing to bridges, this comprehensive survey details every aspect of this brave new cycling world. Drawing on the latest trends in bike design and fashion it places each project in context to provide an eclectic visual record of the world built around cycling. With an introductory essay that considers the history and future of cycling and packed with numerous color illustrations, this book is perfect for design enthusiasts and cyclists alike.
Adlib record nr. 530011049
boek
Keywords: hedendaags